INTEREST IN THE PUBLIC ACCOUNTANT PROFESSION: THE ROLE OF MOTIVATION AS MODERATION - Nurhayati, Enung; Purnama, Dendi; Nurhayati, Neni; Rahmawati, Teti (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2024)
ABSTRACTThis research aims to examine the influence of job market considerations, professional recognition, professional training and self-efficacy on interest in choosing the profession of Public Accountant and examine the influence of motivational variables as a moderator on interest in choosing a profession as a public accountant. The data used is primary data collected by filling out questionnaires to 317 respondents. The research results found that job market considerations, professional recognition, professional training have a significant positive impact on interest in choosing a profession as a public accountant. However, self-efficacy has a significant negative effect on Interest in the Public Accounting Profession. Motivation strengthens the influence of job market considerations, professional training recognition, self-efficacy on interest in choosing a profession as a public accountant. The implications of the results of this research indicate that students tend to choose the profession of public accountant by looking at good job opportunities and economic considerations.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh pertimbangan pasar kerja, pengakuan profesional, pelatihan profesional dan efikasi diri terhadap minat memilih Profesi Akuntan Publik dan menguji pengaruh variable motivasi sebagai moderasi terhadap minat memilih profesi sebagai akuntan publik. Data yang digunakan adalah data primer yang dikumpulkan dengan pengisian kuesioner kepada 317 responden. Hasil penelitian menemukan bahwa pertimbangan pasar kerja, pengakuan profesional, pelatihan profesional memiliki dampak positif yang signifikan terhadap minat memilih profesi sebagai akuntan publik. Namun, efikasi diri memiliki efek negatif yang signifikan terhadap Minat Profesi Akuntan Publik. Motivasi memperkuat pengaruh pertimbangan pasar kerja, pelatihan profesional pengakuan, efikasi diri terhadap minat memilih profesi sebagai akuntan publik Implikasi dari hasil penelitian ini menunjukkan bahwa mahasiswa cenderung memilih profesi akuntan publik dengan melihat peluang kerja dan pertimbangan ekonomi yang baik.